Identification of the 3D Vibratory Motion of a Rigid Body by Accelerometer Measurements - Francesca Di Puccio; Paola Forte (Shock and Vibration)
The identification of the motion of a rigid body by means of linear accelerometers is a problem already investigated by many researchers, but still debated. The optimisation of the number and placement of accelerometers is also another important aspect of the problem. In this study, an experimental procedure is proposed and applied to identify the rigid-body vibratory motion of the steering wheel of a sporting car, by means of six linear accelerometers. Some numerical simulations for investigating possible errors are also presented.